El Salvador Financial Sector Assessment Program Update : Financial Inclusion - World Bank; International Monetary Fund (Washington, DC, 2017)
Financial service provision has expanded since the 2004 financial sector assessment program (FSAP) update, but access to financial services can expand greatly through mobile banking. An estimated 47 percent of adults in El Salvador have deposit accounts at a regulated financial institution, similar to the Latin American average. Although a range of range of bank and non-bank institutions serve the micro and Small and Medium Enterprises (SME) finance market, significant financial services provision is occurring outside of the regulatory perimeter. Improvements in credit information systems, simplification of credit documentation processes, and a strengthened legal framework for factoring can help facilitate SMEs access to credit. Issues of financial transparency and consumer protection are of increasing importance to the Salvadoran authorities, although resources for enforcement are limited. Both public and private entities are engaging in educational activities to promote financial literacy have the potential to play an important role in curbing over indebtedness. However, the consumer defense agency (Defensoria al Consumidor) lacks sufficient resources for enforcement of consumer protection laws. This paper is divided into following six parts: first part gives overview of financial access and usage patterns; the second part gives information on funding and savings products commercialized; the third part gives market participants; fourth part is legal and regulatory impediments to credit; fifth part deals with supervisory and regulatory perimeter issues; and sixth part is transparency, consumer protection, and financial literacy.